Resource Windfalls, Political Regimes, and Political Stability - Caselli, Francesco; Tesei, Andrea (The Review of Economics and Statistics, 2016)
We study theoretically and empirically whether natural resource windfalls affect political regimes. We show that windfalls have no effect on democracies, while they have heterogeneous political consequences in autocracies. In deeply entrenched autocracies, the effect of windfalls is virtually nil, while in moderately entrenched autocracies, windfalls significantly exacerbate the autocratic nature of the political system. To frame the empirical work, we present a simple model in which political incumbents choose the degree of political contestability and potential challengers decide whether to try to unseat the incumbents. The model uncovers a mechanism for the asymmetric impact of resource windfalls on democracies and autocracies, as well as the the differential impact within autocracies.